Penilaian Kualitas Air Tanah di Kecamatan Jenu Kabupaten Tuban Berdasarkan Indeks Kualitas Air Irigasi - Hari Siswoyo; Joko Kurniawan (Universitas Batanghari Jambi, 2021)
The groundwater used for irrigation must have the quality according to its designation. The objective of this study was to assess the appropriateness of groundwater quality used as a source of irrigation water. This study was conducted on agricultural land in an area close to the coast and potentially intruded by sea water. The location of this study was groundwater irrigation land in the irrigation area of production wells SDTB 063, SDTB 064, and SDTB 342 located in Jenu District, Tuban Regency, East Java Province. Groundwater quality assessment was carried out using the IQWI model. Based on the IWQI value obtained, it can be shown that the groundwater quality from SDTB 064 and SDTB 342 production wells has low water usage restrictions, while the groundwater quality from SDJB 603 production well has moderate water usage restrictions. Groundwater quality with low water usage restrictions can be used as irrigation water on soils with moderate permeability with a recommendation to wash the salt. Groundwater quality with moderate water usage restrictions can be used as irrigation water on soils with moderate to high permeability with a recommendation to wash the salt. Farmers in the study area are recommended to be able to cultivate various alternative of high economic value crops that are suitable with the groundwater quality used as a source of irrigation water as stated in this study, while still making adjustments to agricultural land conditions and climatic conditions.